IMPROVING THE SKILLS OF CHILDREN MOZAIK THROUGH MERONCE IN MEDINA - Elihami Elihami; Suparman Suparman (JURNAL EDUKASI NONFORMAL, 2019)
Early Childhood is a coaching effort aimed at children from birth to the age of six years, which is carried out through the provision of educational stimuli to help physical and spiritual growth and development. This type of research is action research aimed at finding out whether a child's fine motor skills can increase with meronce activities at TPA Medina, Enrekang District, Enrekang Regency.The subject of this research is the children of TPA Medina. This research was conducted using the Kemmis and Mc.Taggart research model consisting of two cycles with each cycle consisting of: planning (planning), implementation (action), observation (observation), and reflection (reflection). Data collected by observation and documentation techniques. The learning steps in this study are the teacher preparing roncean and ropes with shapes that have been adapted to the theme, then the teacher gives examples of how to ronce and distribute roncean and ropes to children.The results showed that the results of the observation of Cycle I showed an increase in children's fine motor skills that was not optimal and had not reached an indicator of success of 80.00%. While the results of the actions in the second cycle increased with a percentage of 94.44% or as many as 15 children got very good criteria. Based on the results of the research that has been done it can be concluded that meronce using beads can improve children's fine motor skills at TPA Medina